Pathogenesis evidence from human and animal models of detrusor underactivity - Jia-Fong Jhang; Yuan-Hong Jiang; Yung-Hsiang Hsu; Han-Chen Ho; Hann-Chorng Kuo (Tzu-Chi Medical Journal, 2022)
Detrusor underactivity (DU) is a common urodynamic diagnosis in patients with lower urinary tract symptoms and large post-voiding residual volume. Animal and human studies showed the possible etiologies of DU include central or peripheral nerve injury, bladder outlet obstruction, chronic ischemia, aging, diabetes mellitus, and sympathetic inhibition of micturition reflex. Evidence from animal and human DU studies with various etiologies revealed highly similar gross and histological characteristics in the bladders, including increased bladder weight, bladder wall thickening, inflammation, collagen deposition, and fibrosis. In electron microscopy, smooth muscle destruction, swollen mitochondria, decreased nerve innervation, caveolae, and umbrella cell fusiform vesicles were noted in the DU bladders. Most animal DU models demonstrate detrusor contractility changes from compensatory to the decompensatory stage, and the change was compatible with human DU observation. The cystometry in the DU animal studies is characterized by impaired contractility, prolong intercontraction interval, and hyposensation, while in vitro bladder muscle strips experiment may exhibit normal detrusor contractility. Decreased bladder blood flow and increased oxidative stress in bladders had been proved in different animal DU models, suggesting they should be important in the DU pathogenesis pathway. Sensory receptors mRNA and protein expression changes in DU bladders had been observed in both animal and human studies, including muscarinic receptors M2, M3, adrenergic receptor β3, purinergic receptor P2X1, P2X3, and transient receptor potential vanilloid (TRPV) 1 and TRPV4. Although some of the sensory receptors changes remain controversial, it might be the target for further pharmacologic treatments.